Cross-neutralization ability of anti-MERS-CoV monoclonal antibodies against a variety of merbecoviruses - Pan, Lin; Kaku, Yu; Tolentino, Jarel Elgin; Kosugi, Yusuke; Sato, Kei (Frontiers in Microbiology, 2025)
In the 21st century, three severe human coronavirus infections have occurred. One of them is the Middle East respiratory syndrome coronavirus (MERS-CoV), a merbecovirus belonging to the family Coronaviridae, is a human pathogenic coronavirus first detected in 2012. Several monoclonal antibodies (mAbs) have been developed for both therapeutics and prevention of MERS-CoV infection. However, the extent to which these anti-MERS-CoV antibodies neutralize other merbecoviruses remains unclear. Here, we evaluated the cross-neutralization ability of ten anti-MERS-CoV mAbs against the pseudoviruses with the spike proteins of five merbecoviruses known to bind to dipeptidyl peptidase 4 (DPP4): three clades of MERS-CoV, a bat-derived merbecovirus (BtCoV-422) and a pangolin-derived merbecovirus (MjHKU4r-CoV). We show that all eight mAbs targeting the receptor-binding domain (RBD) potently neutralize all MERS-CoV clades, but not BtCoV-422 and MjHKU4r-CoV. Of these, the neutralization potency of one mAb, m336, against the MERS-CoV clade B declined due to the V530L substitution detected in certain isolates during the 2015 outbreak in South Korea. On the other hand, although BtCoV-422 was neutralized by the two non-RBD mAbs, 7D10 (targeting the N-terminal domain) and G4 (targeting the S2 subunit), MjHKU4r-CoV found to be resistant. Our findings suggest that combining multiple mAbs targeting different epitopes could be a promising strategy for prevention of future outbreaks caused by novel pathogenic merbecoviruses.